2017
DOI: 10.3390/nu9060596
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Resveratrol Supplementation and Endothelial Function during the Fasting and Postprandial Phase: A Randomized Placebo-Controlled Trial in Overweight and Slightly Obese Participants

Abstract: Studies on the effects of the long-term intake of trans-resveratrol on vascular function are conflicting. In addition, postprandial effects of long-term trans-resveratrol intake on endothelial function are not known. We therefore supplemented 45 overweight and slightly obese volunteers (25 men and 20 women) with a mean (±SD) age of 61 ± 7 years and body mass index of 28.3 ± 3.2 kg/m2 in random order trans-resveratrol (2 × 75 mg/day) or placebo capsules for 4 weeks, separated by a washout period of at least 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In another study, RV in red wine was associated with improved levels of glucose and triglycerides, as well as a lower heart rate, whereas no effect was observed for total cholesterol, HDL, LDL, and high blood pressure [57]. However, in overweight individuals, the intake of 150 mg per day of RV for four weeks did not influence metabolic risk markers such as endothelial function or inflammation, which are related to cardiovascular health risk [58,59]. A possible reason for the contrasting results could be related to the ingested dose of RV, because a positive effect of RV in higher doses on other diseases has been observed.…”
Section: Different Health Effects Of Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, RV in red wine was associated with improved levels of glucose and triglycerides, as well as a lower heart rate, whereas no effect was observed for total cholesterol, HDL, LDL, and high blood pressure [57]. However, in overweight individuals, the intake of 150 mg per day of RV for four weeks did not influence metabolic risk markers such as endothelial function or inflammation, which are related to cardiovascular health risk [58,59]. A possible reason for the contrasting results could be related to the ingested dose of RV, because a positive effect of RV in higher doses on other diseases has been observed.…”
Section: Different Health Effects Of Resveratrolmentioning
confidence: 99%
“…A possible reason for the contrasting results could be related to the ingested dose of RV, because a positive effect of RV in higher doses on other diseases has been observed. However, it is important to note that the first mentioned work [26] had a significantly lower number of participants than the last one [58,59].…”
Section: Different Health Effects Of Resveratrolmentioning
confidence: 99%
“…Five studies presented results missing primary outcome data for either pre-or post-trial measures and were contacted to request full details, with data being added to extracted data if provided [107,111,120,131,132]. In addition, two pairs of studies were found to be using data collected within an identical study cohort, consequentially the data were combined into a single entry in the final dataset [29,122,133,123].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Indeed, animal studies in healthy subjects or disease models of hypertension, type II diabetes and metabolic syndrome, have shown improvements in blood pressure and vascular function following chronic supplementation with both whole extract polyphenols and pure compounds including resveratrol, quercetin and pterostilbene [6-8, 24, 26]. In contrast, in healthy human populations there is a consistent lack of efficacy on vascular outcomes [27,28], but greater variability in the beneficial responses within clinical populations, including type II diabetes, obesity and hypertension [17,19,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also observed a linear relationship ( P < 0.01, R 2 = 0.08) between log10 of plasma resveratrol concentration and acute FMD [ 129 ]. van der Made and collaborators, conversely, observed that transresveratrol (150 mg/day for 4 weeks) did not affect fasting or postprandial FMD and plasma biomarkers of endothelial function or inflammation in overweight and slightly obese subjects ( n = 45) as compared to placebo [ 130 ]. A higher dose of transresveratrol (300 mg) acutely and significantly improved FMD in women but not in men with hypertension and baseline endothelial dysfunction [ 131 ].…”
Section: Polyphenolsmentioning
confidence: 99%